Rapid Sequencing of Multiple RNA Viruses in Their Native Form - Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Taylor, Mariah K.; Lee, Jasper; Tolardo, Aline Lavado; Parvathareddy, Jyothi; Kandel, Sangam; Wadley, Taylor D.; Kaewnapan, Bualan; Athipanyasilp, Niracha; Skidmore, Andrew; Chung, Donghoon; et al. (Frontiers in Microbiology, 2019)
Long-read nanopore sequencing by a MinION device offers the unique possibility to directly sequence native RNA. We combined an enzymatic poly-A tailing reaction with the native RNA sequencing to (i) sequence complex population of single-stranded (ss)RNA viruses in parallel, (ii) detect genome, subgenomic mRNA/mRNA simultaneously, (iii) detect a complex transcriptomic architecture without the need for assembly, (iv) enable real-time detection. Using this protocol, positive-ssRNA, negative-ssRNA, with/without a poly(A)-tail, segmented/non-segmented genomes were mixed and sequenced in parallel. Mapping of the generated sequences on the reference genomes showed 100% length recovery with up to 97 % identity. This work provides a proof of principle and the validity of this strategy, opening up a wide range of applications to study RNA viruses.